Automatic assembly design project 1968/9: report of technical survey committee - LeHunte, G. G.; Stout, K. J.; Charnley, C. J.; Powell, E. A. (College of Aeronautics)
An Industrial survey has been carried out to determine the desired features of an automatic as machine. A questionnaire was circulated to industry and the results of the 38% response obtained were analysed and plotted. From these, conclusions were drawn as to the industrial requirements of an assembly machine.